1995
DOI: 10.1074/jbc.270.48.28897
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of MEK5 and Differential Expression of Alternatively Spliced Forms

Abstract: The prototype mitogen-activated protein (MAP) kinase module is a three-kinase cascade consisting of the MAP kinase, extracellular signal-regulated protein kinase (ERK) 1 or ERK2, the MAP/ERK kinase (MEK) MEK1 or MEK2, and the MEK kinase, Raf-1 or B-Raf. This and other MAP kinase modules are thought to be critical signal transducers in major cellular events including proliferation, differentiation, and stress responses. To identify novel mammalian MAP kinase modules, polymerase chain reaction was used to isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
188
1
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(203 citation statements)
references
References 66 publications
10
188
1
4
Order By: Relevance
“…We demonstrated a strong, linear correlation between MEK5 and ERK5 protein expression in matched cases (P ¼ 0.0053). This close relationship ties in with current knowledge of ERK5 as the specific substrate for MEK5, and pMEK5 as the only known activating molecule of ERK5 (English et al, 1995;Mody et al, 2003). We have demonstrated a significant correlation between ERK5 cytoplasmic overexpression and Gleason sum score (Po0.0001), an observation not seen for MEK5 expression (Mehta et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We demonstrated a strong, linear correlation between MEK5 and ERK5 protein expression in matched cases (P ¼ 0.0053). This close relationship ties in with current knowledge of ERK5 as the specific substrate for MEK5, and pMEK5 as the only known activating molecule of ERK5 (English et al, 1995;Mody et al, 2003). We have demonstrated a significant correlation between ERK5 cytoplasmic overexpression and Gleason sum score (Po0.0001), an observation not seen for MEK5 expression (Mehta et al, 2003).…”
Section: Discussionsupporting
confidence: 80%
“…MAP kinase kinases (MEKs/MAPKKs) represent protein kinases upstream of MAPKs, critically controlling cellular proliferation and apoptosis. Mitogen/extracellular signal-regulated kinase kinase-5 (MEK5) is the most recently identified MAPKK and specifically activates ERK5, also known as Big MAP kinase 1 (English et al, 1995;Zhou et al, 1995). The ability of inhibitors of the classical MAPK (ERK1/2) cascade to block ERK5 activation suggested that ERK5 might regulate some cellular functions originally attributed to ERK1/2.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the functional signi®cance of this pathway in relation to other MKK-signaling pathway remains unclear, it is signi®cant to note here that p38MAPK and ERK2 can also phosphorylate and activate MEF2C. In this context, it is interesting to note that MKK5 and ERK5 are highly expressed in cardiac skeletal muscle (Zhou et al, 1995;English et al, 1995) while MEF2 family of transcription factors are mainly expressed in skeletal muscle and brain tissue (Martinet et al, 1994;McDermott et al, 1994). Taken together, these observation may be indicative of the critical role played by MKK5-ERK5 signaling pathway in cardiac physiology (Zhou et al, 1995).…”
Section: Map Kinase Kinase-5mentioning
confidence: 82%
“…It is interesting to note that the 23-amino acids encoded by 5' exon in the larger a-isoform is similar to the sequence found in proteins which associate with the actin cytoskeleton. This may be indicative of the isoform-speci®c subcellular localization of MKK5 (English et al, 1995). Interestingly, ERK5 also shows a distinct structural motif consisting of Pro-Ala repeats.…”
Section: Map Kinase Kinase-5mentioning
confidence: 98%
See 1 more Smart Citation